Monday

April 21, 2014

April 21, 2014

Posted by **janelle** on Wednesday, January 26, 2011 at 6:03pm.

3a^2bx(?)=6a^2b^2x

- algebra2 -
**janelle**, Wednesday, January 26, 2011 at 6:07pm(?)=b

- algebra2 -
**helper**, Wednesday, January 26, 2011 at 7:11pmYes, b is the missing variable.

But 3a^2b^2x still does not = 6a^2b^2x

6a^2b^2x = 6a^2b^2x

**Related Questions**

Pre-Calc-please check - Please check this for me expand (3z-2b)^5 using Binomial...

algebra - Given g(x) = –2x – 1, find g(3a). G(3a)=-2(3a)-1 = -6a-1 = -5 is this ...

Math - Could you please check my answer? Subtract: (6a+2b-5c)-(3a+2c) My answer ...

math - 3a^2b + 6a^2b 9a^4b^2

Math - 6a(3a-2) + 12b(3a-2) Is it correct if i multiplied 6a by 3a then 6a by -2...

alg - Find the sum. Express your answer in simplest form. (14a^2 / 2b) + (3a / ...

math binomial expansion - binomial expansion (3a^2-2b^3)^4 is this right? (3a^2...

Math- factoring - Show all work and factor completely. 6a^2+5a-4 (6a^2+8a)-(3a-4...

math,help - I need help factoring this out 6a^2-5a+1 so far what i have is this...

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...